3 - Sociology and Social Work in Nigeria: Characteristics, Collaborations and Differences - Ayodele Ogundipe; Patrick A. Edewor (African Sociological Review, 2013)
This paper presents the evolution of sociology and social work in Nigeria and examines the current characteristics and areas of convergences and divergences in both fields. It was only in the 1960s that universities in Nigeria began to offer degree programmes in sociology with the first sub-department and full department of sociology established at the University of Ibadan and the University of Nigeria, Nsukka respectively in 1960. These were followed by the other first generation universities and subsequently, the newer universities. There are now scores of Nigerian universities that offer degree programmes in sociology both at the undergraduate and post-graduate levels. In discussing the characteristics of sociology and social work, the paper examines the teaching of sociology and generic social work at the tertiary level in two universities and the national social work policy and its limited implementation by the Ministry of Social Development under which social work is placed. This provides a reasonably clear picture of the current situation of sociology and social work in Nigeria. The findings show that the teaching of social work employs considerable sociological theories and sociology students are influenced by their exposure to social work. Some universities accept/approve the situating of social work in sociology departments for now. Social welfarism remains an area to be implemented in the future.